Primary sternal osteomyelitis caused by Nocardia nova: case report and literature review - Baraboutis,Ioannis G. (2008)
A 51 year old woman without significant past medical history or risk factors for Nocardia infection developed primary Nocardia nova sternal osteomyelitis with mediastinal abscess, diagnosed with open biopsy. She required prolonged antibiotic therapy and had a favorable outcome. Primary sternal osteomyelitis develops in the absence of a contiguous focus of infection, as opposed to secondary sternal osteomyelitis, which is usually a complication of sternotomy. Staphylococcus aureus probably still is the most common cause of both forms of sternal osteomyelitis. Nocardia species invade humans usually through the respiratory tract and can cause a variety of localized infections through the hematogenous route. Pulmonary involvement may or may not coexist. Immunosuppressed patients are more prone to infection by Nocardia species, although cases involving seemingly immunocompetent patients are not rare. This is the first reported case in the English literature of primary sternal osteomyelitis due to Nocardia nova or any other Nocardia species.